Odpowiedzi

2010-02-17T21:36:33+01:00
A)x/3 + y/2=1 /*6
x-y=6

2x+3y=1
x-y=6 /*3

2x+3y=1
+3x-3y=18
5x=19 /÷5
x=3⅘
y=3⅘-6=-2⅕

b)2x+y=6
x/4-y/5=4 /*20

2x+y=6 /*4
5x-4y=4

8x+4y=6
+5x-4y=4
13x=10 /÷13
x=10/13
y=6-2*¹⁰₁₃=6-1⁷₁₃=4⁶₁₃

d)3x-3y+3=0
x+½y-2=0 /*6

3x-3y+3=0
+6x+3y-12=0
9x-9=0
9x=0+9
9x=9 /÷9
x=1
3*1-3y+3=0
-3y=0-3-3
-3y=-6 /÷-3
y=2

e)4x-2y=6 /*3
3x+6y=12

12x-6y=18
+3x+6y=12
15x=30 /÷15
x=2
y=12-3*2
y=6

f)3x-4y=14 /*2
-2x+7y=-18 /*3

6x-8y=28
+ -6x+21y=-54
13y=-26 /÷13
y=-2
3x-4*(-2)=14
3x+8=14
3x=14-8
3x=6 /÷3
x=2
2010-02-17T21:39:35+01:00
D)3x-3y+3=0
x+1/2y-2=0/*-3

-3y+3/2y+9=0 to y=6 to x=5
e)4x-2y=6 to 2x-y=3/*2
3x+6y=12 to x+2y=4
5x=10 to x=2 to y=1

f) 3x-4y=14/*2 to 6x-8y=28
-2x+7y=-18/*3 to-6x+21y=-54
13y=-26 to y=-2 to x=2